Length-weight relationships of Indian squid, Uroteuthis duvaucelii and Bigfin reef squid, Sepioteuthis lessoniana from the coastal waters of Langkawi Island, Malaysia - Rohizad Maidin Mohd Samsul; Mastura Mustapha; Atikah Harun Nadiayatul; Wahab Abdullah Abdul; Luqman Wan Rosdi Wan Muhammad; Asyraf Raja Omar Raja Hanif; Faizah Ismail; Haryati Abd. Wahab; Bakri Miswan (E3S Web of Conferences)
Studies on the length-weight relationship (LWR) are crucial for understanding the growth, health, and ecological dynamics of fish and cephalopod populations. This study investigates how weight varies relative to its length. There have been limited studies on LWR in cephalopods, especially in Malaysia. This research aimed to explore the size frequency, length-weight relationship and relative condition factor of Uroteuthis duvaucelii and Sepioteuthis lessoniana in Langkawi Island. The samples were caught using squid cast net with a mesh size of 1.0 to 1.5 inch. Linear regression analysis was used to established the LWR of the species. Maximum mantle length for U. duvaucelii was recorded to be 213 mm long, and 98 mm for S. lessoniana. The growth coefficient b values calculated for U. duvaucelii and S. lessoniana were 2.068 and 2.3839, respectively, indicating negative allometric growth in this region. The mean relative condition factor (Kn) obtained for U. duvaucelii and S. lessoniana was similar, approximately 1.0 ± 0.1 suggesting favorable life conditions. The findings from this study are valuable in managing and conserving these species in Langkawi Island, Kedah.